Výroba repliky litinového hmoždíře - Myška, Martin (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2015)
Tato bakalářská práce se zabývá kompletní technologií výroby repliky hmoždíře. V první části je popsán historický vývoj hmoždíře v Čechách a ve světě. V druhé části je popsán technologický proces výroby modelů a způsobů formování. Nakonec je zdokumentována výroba formy, následné odlití a očištění hmoždíře.

This bachelor thesis deals with the complete production technology of mortar replica. The first part describes the historical development of mortar and pestle in Bohemia and in the world. In the second part there is the description of the technological process of production of models and the methods of molding process. Finally, the production of the mold, subsequent casting and purifying process of the mortar are documented.
Manufacture of cast iron mortar replica
Keywords: hmoždíř a tlouk; formování; modelové zařízení; odlévání; výroba repliky hmoždíře; mortar and pestle; molding process; model device; casting; manufacture of mortar replica